2015
DOI: 10.1145/2829944
|View full text |Cite
|
Sign up to set email alerts
|

Designing Interactions with Multilevel Auditory Displays in Mobile Audio-Augmented Reality

Abstract: Auditory interfaces offer a solution to the problem of effective eyes-free mobile interactions. In this article, we investigate the use of multilevel auditory displays to enable eyes-free mobile interaction with indoor location-based information in non-guided audio-augmented environments. A top-level exocentric sonification layer advertises information in a gallery-like space. A secondary interactive layer is used to evaluate three different conditions that varied in the presentation (sequential versus simulta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…Our literature review showed that indoor and outdoor exploration activities were of the highest importance. Most research towards improving indoor exploration has been applied to locations such as museums, art galleries, or for virtual search tasks in a physical space (Bederson, 1995;Heller et al, 2016;Rumiński, 2015;Vazquez-Alvarez et al, 2016). Outdoor exploration studies focusing on providing enhanced experiences of events from the past, recreating soundscapes to supplement an existing experience such as that of a safari or providing information about their surroundings to tourists in a meaningful way, have also been conducted in attempts to improve the effectiveness of the auditory information being provided (Boletsis & Chasanidou, 2018;Lawton et al, 2020;Vazquez-Alvarez et al, 2012).…”
Section: Preliminary Focus Groupmentioning
confidence: 99%
“…Our literature review showed that indoor and outdoor exploration activities were of the highest importance. Most research towards improving indoor exploration has been applied to locations such as museums, art galleries, or for virtual search tasks in a physical space (Bederson, 1995;Heller et al, 2016;Rumiński, 2015;Vazquez-Alvarez et al, 2016). Outdoor exploration studies focusing on providing enhanced experiences of events from the past, recreating soundscapes to supplement an existing experience such as that of a safari or providing information about their surroundings to tourists in a meaningful way, have also been conducted in attempts to improve the effectiveness of the auditory information being provided (Boletsis & Chasanidou, 2018;Lawton et al, 2020;Vazquez-Alvarez et al, 2012).…”
Section: Preliminary Focus Groupmentioning
confidence: 99%
“…However, multiple users had to move in sync for the audio to begin and stop playing at the same time for each user. This concept was taken a step further by Vazquez-Alvarez et al (2016) in which one layer of sonification was audible to users to attract their attention towards respective artifacts, and a second interactive layer of sound started to play as users would get closer to them. Such applications of audio to enhance users' experiences fit the three dimensions of AAR.…”
Section: Related Workmentioning
confidence: 99%
“…In addition to engineering, it has good applications in medical, education, and entertainment [18]. Multiple modalities can be implemented for improving the AR experience [19]. However, the lack of suitable hardware and software usually constrains AR applications to fixed 2D screens or requires the use of intrusive markers [20].…”
Section: Related Workmentioning
confidence: 99%